Analysis of Alternative National Ambient Carbon Monoxide Standards - Keeney, Ralph L.; Sarin, Rakesh K.; Winkler, Robert L. (Management Science, 1984)
A risk assessment model is developed to relate adverse health effects to alternative carbon monoxide standards. The analysis requires information in the form of available data and expert judgments concerning factors such as ambient CO level, human exposure to CO, physiological responses, and dose-response relationships. Quantitative estimates, including probabilities, are obtained for selected summary measures of adverse health effects.